The Structure of the Permanent Job Wage Premium: Evidence from Europe - Lawrence M. Kahn (Institute for the Study of Labor (IZA), 2013)
Using longitudinal data on individuals from the European Community Household Panel (ECHP) for thirteen countries during 1995-2001, I investigate the wage premium for permanent jobs relative to temporary jobs. The countries are Austria, Belgium, Denmark, Finland, France, Germany, Greece, Ireland, Italy, the Netherlands, Portugal, Spain, and the United Kingdom. I find that among men the wage premium for a permanent vs. temporary job is lower for older workers and native born workers; for women, the permanent job wage premium is lower for older workers and those with longer job tenure. Moreover, there is some evidence that among immigrant men, the permanent job premium is especially high for those who migrated from outside the European Union. These findings all suggest that the gain to promotion into permanent jobs is indeed higher for those with less experience in the domestic labor market. In contrast to the effects for the young and immigrants, the permanent job pay premium is slightly smaller on average for women than for men, even though on average women have less experience in the labor market than men do. It is possible that women even in permanent jobs are in segregated labor markets. But as noted, among women, the permanent job wage premium is higher for the young and those with less current tenure, suggesting that even in the female labor market, employers pay attention to experience differences.
Keywords: J31; J42; 330; wage structure; segmented labor markets; temporary jobs